Komposisi Jenis Dan Fluktuasi Kelimpahan Plankton Secara Temporal Di Perairan Selat Lombok - Putu Maya Witariningsih; Yulianto Suteja; I Nyoman Giri Putra (Fakultas Kelautan dan Perikanan Universitas Udayana, 2020)
Indonesian Throughflow (ITF) is a circulation of water mass in Indonesian, water are carrying from the Pacific Ocean to the Indian Ocean. When the water mass from the Pacific Ocean to Indonesian waters will mix with the water mass of Indian Ocean. One of the outflow is the Lombok Strait. The mixing of process bring nutrient-rich in bottom layer to rise to the upper layer and it will affect the fertility. One indicator of water fertility by measuring the abundance and distribution of plankton. The aims of this study to determine the temporal of composition species and fluctuations of plankton abundance temporally in the waters of the Lombok Strait. The study was conducted in the Lombok Strait in November 2017. Data was collected at one point and sample was only take on the surface of the waters. The genus composition of the most widely found phytoplankton Bacillariophyceae class (19 genera) and from the widely obtained zooplankton Hexanauplia class (7 genera). The highest abundance of phytoplankton occurs during high tide during afternoon. This phenomenon is caused by photosynthesis of phytoplankton in the water surface. In contrast to the abundance of the highest zooplankton occurs during high tide in the early morning. This is caused by zooplankton's daily vertical migration and negative phototaxis. Comparison of phytoplankton abundance with zooplankton abundance is inversely proportional, zooplankton abundance depends on abundance of phytoplankton, because phytoplankton grow faster by cell substraction, compared to phototaxis of in zooplankton. It is also a predation of phytoplankton by zooplankton.